Calcium Signaling and Gliotransmission in Normal vs. Reactive Astrocytes - Agulhon, Cendra; Sun, Min-Yu; Murphy, Thomas; Myers, Timothy; Lauderdale, Kelli; Fiacco, Todd A. (Frontiers in Pharmacology, 2012)
A prominent area of neuroscience research over the past 20 years has been the acute modulation of neuronal synaptic activity by Ca2+-dependent release of the transmitters ATP, D-serine, and glutamate (called gliotransmitters) by astrocytes. Although the physiological relevance of this mechanism is under debate, emerging evidence suggests that there are critical factors in addition to Ca2+ that are required for gliotransmitters to be released from astrocytes. Interestingly, these factors include activated microglia and the proinflammatory cytokine Tumor Necrosis Factor α (TNFα), chemotactic cytokine Stromal cell-Derived Factor-1α (SDF-1α), and inflammatory mediator prostaglandin E2 (PGE2). Of note, microglial activation and release of inflammatory molecules from activated microglia and reactive astrocytes can occur within minutes of a triggering stimulus. Therefore, activation of astrocytes by inflammatory molecules combined with Ca2+ elevations may lead to gliotransmitter release, and be an important step in the early sequence of events contributing to hyperexcitability, excitotoxicity and neurodegeneration in the damaged or diseased brain. In this review, we will first examine evidence questioning Ca2+-dependent gliotransmitter release from astrocytes in healthy brain tissue, followed by a close examination of recent work suggesting that Ca2+-dependent gliotransmitter release occurs as an early event in the development of neurological disorders and neuroinflammatory and neurodegenerative diseases.